The use of digital technologies for babies: reading in the educational field - Pereira do Nascimento Bittencou, Cleonice (2019)
This production is added in the educational scene and in the field of articulations between psychoanalysis and education. It shows brief reflections on the digital technologies use for babies and their effects on social linking, based on the teaching experience of the first author in a public school in the Federal District - Brazil, which motivated her doctoral studies. We believe that the continuous training of teachers to guide the social relationships of the child, his parents and families, regarding the technology can be for emergency, when we are dealing with infants and children in their early childhood.